Hydrolysable Tannin Supplementation Alters Digestibility and Utilization of Dietary Protein, Lipid, and Carbohydrate in Grass Carp (Ctenopharyngodon idellus) - Yao, Jingting; Chen, Peng; Apraku, Andrews; Zhang, Gaigai; Huang, Zhongyuan; Hua, Xueming (Frontiers in Nutrition, 2019)
Tannin, an antinutritional component of plant proteins was fed to grass carp (Ctenopharyngodon idellus, 8.18 ± 0.81g) for eight-week to investigate their tolerance levels. Semi-purified diets (T0, T1, T2 and T3) with varying levels of hydrolysable tannin (0, 0.75, 1.25 and 1.75% respectively) were used. No significant difference was obtained in weight gain, while feed conversion ratio of T0 was significantly lower than T2. Muscle protein content of T0 and T3 were significantly higher than T2, while lipid content of T0 was significantly higher than other groups. Muscle and hepatic glycogen in T0 were significantly lower than other groups. Muscle saturated fatty acids in T3 were significantly higher than T0, and lowest in T1 and T2, while the poly-unsaturated fatty acids in T1 and T2 were higher than T0 and lowest in T3. Significant increases were obtained in trypsin and amylase activities as tannin levels increased, the lipase activity of T0 and T1 was significantly higher than T2 and T3. Activities of hepatic alanine aminotransferase and aspartate aminotransferase decreased with increasing tannin level. The total protein in serum of T2 was significantly higher than T0 and T1 and lowest in T3, whereas globulin of T2 was significantly higher than T0 and T3 and lowest in T1, while albumin of T1 was significantly higher than other groups. Urea nitrogen of T0 was significantly higher than other groups, triglyceride and total cholesterol significantly increased with tannin level and decreased in T3, significant decreases were obtained in low-density lipoprotein cholesterol and high-density lipoprotein cholesterol in T3. mRNA expression of intestinal TOR was significantly upregulated as dietary tannin increased. In hepatopancreas, the expression of glucokinase in T1 was significantly higher than T2, and lowest in T0 and T3, pyruvate kinase in T2 was significantly higher than T0 and T1 and lowest T3. The expression of lipoprotein lipase upregulated as tannin level and downregulated in T3, and fatty acid synthase downregulated as tannin level. In conclusion, grass carp could tolerate 1.75% dietary tannin without influencing growth. However, 1.25% tannin impaired digestion and metabolism of protein, decreased the deposition of lipid and promoted utilization of carbohydrate.